INVESTIGATING THE ROLE OF PROBIOTICS AND SHORT-CHAIN FATTY ACIDS (SCFAs) IN MODULATING LEPTIN FOR IMPROVED ANTI-DIABETIC EFFECTS IN STREPTOZOTOCIN-NICOTINAMIDE INDUCED TYPE II DIABETES IN RATS - DEVI, P. RAJYALAKSHMI; SRINATH, MOTE; REDDY, B. MAHESHWARI; CHAITANYA, KOPPALA R. V. S; VINYAS, M. (International Journal of Applied Pharmaceutics, 2025)
Objective: The gut microbiota, such as Lactobacillus rhamnosus and Bifidobacteriumlongum produces short-chain fatty acids like acetate, propionate, and butyrate from fermentation of undigested fiber, holds promise for managing metabolic diseases, including type II diabetes and obesity. This study explores the potential of probiotics and short-chain fatty acids to modulate leptin for increased anti-diabetic action in rats, offering hope for future diabetes management strategies. Methods: Rats weighing 150 and 200 g were chosen for the study, divided into multiple groups, and given a single dose of nicotinamide and streptozotocin to induce type II diabetes. Probiotics, butyrate, propionate, and glibenclamide were continually given to respective groups after the induction of Type II diabetes. Every week, the animal's body weight was determined. Following the study's conclusion, blood was drawn via retro-orbital puncture to test the following parameters: insulin, leptin, lipid, liver, and kidney profiles. Liver and pancreas were isolated for histopathological analysis. Results: In rats with type II diabetes, fasting blood glucose levels were significantly increased (p<0.001) compared with the normal control group, accompanied by a marked reduction in fasting insulin and leptin levels (p<0.001). Treatment with selected probiotics, butyrate, and propionate caused a significant reduction in blood glucose (p<0.001) and a significant increase in fasting insulin and leptin levels (p<0.001), indicating improved pancreatic function relative to diabetic controls. Diabetic rats displayed severe diabetic dyslipidaemia, with elevated atherogenic lipoproteins and reduced HDL-C (p<0.001). Administration of probiotics, butyrate, and propionate led to a significant reduction in atherogenic lipid levels (p<0.01) and a marked increase in HDL-C compared with diabetic controls. Liver and kidney function markers were significantly elevated in diabetic control rats (p<0.01), whereas these elevations were notably reduced (p<0.01) in all treatment groups. Among these, the combination of butyrate and probiotics exhibited the most pronounced therapeutic benefits (p<0.001 vs. other treatments). Histopathological evaluation revealed severe hepatic and pancreatic abnormalities in diabetic controls, whereas treatment groups exhibited restoration of normal tissue architecture. Notably, butyrate-treated rats showed prominent β-cell hyperplasia and hypertrophy, further supporting enhanced pancreatic regeneration and overall therapeutic efficacy. Conclusion: This finding suggested that butyrate, in combination with probiotics, has more anti-diabetic effects than individual treatment by increasing the levels of Leptin. These results could potentially lead to the development of novel therapeutic strategies for managing type II diabetes.